Effects of Endoscopic Submucosal Excavation With Non-Submucosal Injection on Stromal Tumors in Stomach - Huang, Liang; Jia, Yi-Xin; Lyu, Bin; Meng, Li-Na; Jin, Hai-Feng (Frontiers in Oncology, 2022)
Background and Aims: Endoscopic submucosal excavation (ESE) of gastrointestinal stromal tumors (GISTs) is recently recognized, but the no-submucosal injection (NSI) ESE skill is less known about its efficacy and safety. This study is aimed at assessing the feasibility, clinical efficacy, and safety of NSI-ESE of gastric GISTs. Patients and Methods: Endoscopic removal (ER) of GISTs was performed in 102 patients at our hospital between January 2018 and January 2020. The clinical features, surgical outcomes, complications, pathological diagnosis, and risk classification were evaluated. Results: All GISTs were complete resection by ER, with the complete resection rate of 100%. It was achieved by ESE/ EFTR (endoscopic full-thickness resection) in 49 cases with submucosal injection, and by ESE/ EFTR in 53 cases with NSI-ESE. The mean surgical time in cases with submucosal injection was 25.86 ±4.45 min, compared to the cases without submucosal injection (17.23 ±3.47 min), the difference is significant (P<0.001);the exposure time of tumor, the time of complete excavation of tumor, procedure cost and hospital stay in NSI-ESE group were all lower than those cases with submucosal injection (P<0.05). In the risk classification, 95 (93.1%) were of a very low risk, 4 (4.0%) of a low risk, and 2 (2.0%) of a high risk. No recurrence or metastasis was observed during the follow-up period of 18 ± 6 months (range: 13-25 months). Conclusions: NSI-ESE is a feasible, effective, and safe treatment for gastric GISTs, and compared to the conventional ESE, NSI ESE have advantages in decreasing procedure time and risk of perforation and have good cost-effective.